(untitled) (BIRDEM Medical Journal, 2019)
Mononeuritis multiplex is a common manifestation of many illnesses which includes diabetes, leprosy, malignancy and certain types of systemic vasculitis. The antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a group of rare diseases which show typical characteristic inflammatory cell infiltration and blood vessel wall necrosis. AAV syndromes include granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA) and eosinophilicgranulomatosis with polyangiitis (EGPA). Here we present a patient who presented with mononeuritis multiplex and had features ofEGPA. The patient was treated with standard regimen of steroids and pulsed cyclophosphamide and she achieved good clinical response. Birdem Med J 2019; 9(3): 257-260